Memória de docentes universitários: resistência e luta no campus universitário de Abaetetuba - OLIVEIRA, Mara Rita Duarte de (Universidade Federal do Pará, 2021)
This article is part of a broader research on the teachers of the Abaetetuba University Campus, which aimed to present the results of the research entitled Teaching memory and resistance narratives at the Federal University of Pará, from 2013 to 2017, part of the research financed by PIBIC / UFPA and another carried out without funding. The research was carried out with professors from the Abaetetuba University Campus, with the central objective of interpreting the strategies and devices of teacher resistance to the imposing models of installation of the heteronymous and neo professional University, from the teaching memory focusing on the narratives of the teachers of the Abaetetuba University Campus. Thus, we found that teachers are based on reflection as a way to experience and understand the sphere of the world of life and the system, using intellectual work as an activity of knowledge production and active participation in the University.